Prediksi Spot Price Komoditas Emas Berjangka dengan Pendekatan Vector Error Correction Model - Izma Fahria; Desy Yuliana Dalimunthe; Ririn Amelia; Ineu Sulistiana; Baiq Desy Aniska Prayanti (Department of Mathematics, Universitas Negeri Gorontalo, 2023)
Time series data usually exhibit non-stationary behavior and involve interrelated variables. Thus, we need a model that can obtain good forecasting results from non-stationary time series data with multivariate variables. The Vector Error Correction Model (VECM) is a multivariate time series model which is a vector form of Vector Autoregressive Regression (VAR) for time series data that are non-stationary and have a cointegration relationship. This research was conducted to model the cointegration relationship in providing clarity on the long-term relationship of the influence of future prices and the Covid-19 pandemic on price movements of gold futures commodities and to predict spot price prediction modeling for gold futures commodities. The results of the research using the VECM (2) model, which is the best model, show that the future price of the gold commodity is quite dominant in influencing the value of the spot price of gold. The Covid-19 variable does not have a significant effect on the spot gold price variable.